Management Strategy of Purse Seine Net Fisheries in Pati Regency - Herna Octivia Damayanti (Faculty of Fisheries and Marine Science, Brawijaya University, 2021)
The matter of fishery resources is one of the important problems in the capture fishery development because the condition of most capture fisheries is over exploitation. The research objectives were (1) to analyze the utilization level of fishery resources with Purse Seine nets, and (2) determine the strategy for managing fishery resources with purse seine nets in Pati Regency. The sampling method used simple random sampling with 56 Purse Seine fishermen as a sample size. The research locations consist of Bajomulyo Village and Bendar one in Juwana Subdistrict, Pati Regency. Data analysis used (a) Total Allowable Catch (TAC) calculation, (b) AHP to determine strategy priorities. Research results: the utilization rate is 102.48%, meanwhile management strategies based on the aspect priority order of management for capture fishery resources are human resources, fish resources, infrastructure and institutions, while the priority order based on alternative criteria are the improvement of human resources expertise of ship masters, protection of the stability of fishery commodity prices, improvement of fishing gear operating skills for the boat crews and making adequate boat moorings around the fish auction.